Sebaran Rumpon di Samudera Hindia pada Daerah Penangkapan Purse Seine - Deni Sarianto; Djunaidi; Kadi Istrianto (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2019)
The Fish Aggregating Devices (FADs) have been utilized for a long time by the purse seine fishermen in Sibolga. This research was aimed at mapping the devices operating by the Sibolga fishermen in the Indian Ocean and identifying the dominant captured fish surrounding the set devices. It was carried out in the Nusantara Fishing Port of Sibolga, North Sumatera Province – Indonesia. The results of this research demonstrate that the FADs are set in three fishing grounds in the Indian Ocean of Indonesia namely (1) the waters surrounding Nias Island, (2) Exclusive Economic Zone of Indonesia, and (3) the waters surrounding Mentawai Island. Further, based on the species, the capturedfish dominantly in the surrounding set FADs are skipjack tuna (1,114.196 tons), short pectoral Mackerel (338.344 tons), shortfin scad Mackerel (217.505 tons), Mackerel Tuna (165.67 tons), Sardine (148.786 tons), and Yellowfin Tuna (78.175 tons). Overall, this research infers that the captured fishusing purse seine fishing gear are dominantly represented by the small and medium sizes. Moreover, the potential fishing grounds for Sibolga fishermen are located in the surrounding waters of Nias Island and Mentawai Island.